2013
DOI: 10.1155/2013/569578
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Fibromatosis Presenting as a Diagnostic Dilemma: A Rare Differential Diagnosis of Right Iliac Fossa Mass in an Eleven Year Old—A Rare Case Report

Abstract: An eleven-year-old boy presented with a mass in the right iliac fossa for the last 21 days associated with pain, fever, anorexia, and nausea. The patient was thoroughly investigated and contrast-enhanced CT abdomen revealed a well-defined mass in the region of right iliac fossa. Exploratory laparotomy was done and a mass measuring 10 cm in diameter arising from mesentery of proximal ileum and adherent with the wall of ileum was seen. Resection and anastomosis were done. Histopathological examination showed mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Several case reports have been published whereby fibromatosis presents as an incidental or symptomatic abdominal mass [12,[16][17][18][19][20][21][22][23]. Some present as surgical emergencies with bleeding requiring emergency laparotomy [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have been published whereby fibromatosis presents as an incidental or symptomatic abdominal mass [12,[16][17][18][19][20][21][22][23]. Some present as surgical emergencies with bleeding requiring emergency laparotomy [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenteric fibromatosis (MF), also known as mesenteric desmoids, is part of the clinical-pathologic spectrum of deep fibromatoses which encompasses a group of benign fibroproliferative processes that are locally aggressive and have the capacity to infiltrate or recur without metastasis. They are classified according to their anatomical location, whether it is intra-abdominal, from the deep soft tissues of the abdominal wall, or deep within the extra-abdominal soft tissues [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, after extensive research, we found that a strong association has also been reported between desmoid tumors and familial adenomatous polyposis (FAP), especially Gardner’s syndrome [ 2 ]. Thirteen percent of patients with mesenteric fibromatosis have FAP, specifically the Gardner syndrome variant of FAP [ 1 ]. Therefore, patients with FAP and a family history of mesenteric desmoids have a greater than 25% chance of developing this tumor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations